DETERMINE THE PREVALENCE OF VARIOUS TYPES OF CANCER AND EXAMINE THE MOST FREQUENT CANCER TYPE ACCORDING TO THEIR GENDER - MARWAT, MKUK; GUL, MM; BASHEER, MD; AHMED, F; DILSHAD, M; BURKI, AUH (Biological and Clinical Sciences Research Journal, 2023)
The study aimed to determine the prevalence of different cancer types and identify the most frequent cancer type by gender. The study was conducted retrospectively in the Department of Internal Medicine at Mayo Hospital, Lahore. A total of 522 patients were included in the study, and the data was collected from 10 different cancer hospitals in Pakistan. The study was six months, from January 2023 to June 2023. Statistical analysis was performed using SPSS Version 25. The results showed that Breast cancer was the predominant type of cancer (28.4%), followed closely by Lips oral cavity cancer (23.8%). Colorectum cancer affected 18.0% of patients, while skin cancer was observed in 12.6% of cases. Liver and intrahepatic bile duct, Lung and bronchus, Stomach, and Brain cancer collectively constituted approximately 8.0%, 5.9%, 2.1%, and 1.1%, respectively. The study included 209 (40.0%) male and 313 (60.0%) female patients. The study found that the most common type of cancer differed by gender. Cancers of the lip and oral cavity were the most common in males, while breast cancer was the most frequent cancer type among females.